Application of the SAW (Simple Additive Weighting) Method in the Selection of Foundation Scholarship Recipients at STMIK Mulia Darma - Naibaho, Eltrina (Cattleya Darmaya Fortuna, 2024)
This research aims to apply the Simple Additive Weighting (SAW) method in the selection of Foundation scholarship recipients at STMIK Mulia Darma. Scholarships are a form of financial support given to outstanding or needy students, with the aim of supporting the smooth running of their studies. The SAW method is one of the multi-criteria methods that can be used to choose the best alternative from several existing alternatives. In this study, the alternative in question is students who register to get a Foundation scholarship at STMIK Mulia Darma. The criteria used include Cumulative Grade Point Average (GPA), parents' income, academic achievement, and participation in extracurricular activities. Each criterion is weighted based on its level of importance. The data used in this study is data on students who apply for Foundation scholarships at STMIK Mulia Darma in the 2023/2024 academic year. The data was processed using the SAW method to determine students who are eligible for scholarships. The results of the study show that the SAW method can be used effectively to select students who receive Foundation scholarships at STMIK Mulia Darma. Students who are selected as scholarship recipients are the students who have the highest weight score based on the results of the SAW method calculation.